2018
DOI: 10.1016/j.ijsu.2018.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting hypocalcemia after total thyroidectomy – A retrospective cohort analysis

Abstract: Prolonged surgery time seems to correlate with initial postoperative hypocalcemia independently of the underlying disease and surgical expertise but does not affect the persistence of hypocalcemia. Initial symptomatic postoperative hypocalcemia after total thyroidectomy is associated with a high rate of persistent hypocalcemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 29 publications
0
42
3
2
Order By: Relevance
“…In six studies, age was found to have a statistically significant association with transient biochemical hypocalcaemia, 12,26,30,33,46,47 with four papers reporting this only in younger patients 12,26,30,33 and two papers reporting significance in older patients. 46,47 This is in comparison to 26 studies 11,1619,24,25,2729,31,32,3840,42–44,49,52,54,56,5861 that found no significant association to age.…”
Section: Resultscontrasting
confidence: 62%
See 2 more Smart Citations
“…In six studies, age was found to have a statistically significant association with transient biochemical hypocalcaemia, 12,26,30,33,46,47 with four papers reporting this only in younger patients 12,26,30,33 and two papers reporting significance in older patients. 46,47 This is in comparison to 26 studies 11,1619,24,25,2729,31,32,3840,42–44,49,52,54,56,5861 that found no significant association to age.…”
Section: Resultscontrasting
confidence: 62%
“…These included an increasing number of parathyroid glands left in situ at the time of surgery (significant results in four of four studies 18,28,32,34 ), and evidence of parathyroid glands in the pathology specimen (8 significant results from 12 studies) 20,33,38,42,4649 . However, other surgical factors related to the parathyroid glands do not demonstrate the same connection; a higher number of parathyroid glands identified during the procedure was more frequently not statistically significant (six of nine results were not significant 31,34,40,43,50,51 ) and equivocal results were seen when parathyroid glands are auto-transplanted (nine results significant 19,20,33,38,42,4749,52 , eight non-significant 19,30,50,5357 ). Similarly, the majority of studies which addressed the connection between transient biochemical hypocalcaemia and the extent of thyroidectomy and with neck dissection did not find a statistically significant association.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…3,9,10,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] The quality of all included studies was assessed using the NOS, of which 10 studies were rated as high quality (four with 8 stars and six with 7 stars) and 13 studies were rated as moderate quality (11 with 6 stars and two with 5 stars) (Table 1). 3,9,10,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] According to the heterogeneity for the meta-analyses on preoperative vitamin D levels (I 2 ¼ 74%, P ¼ 0.010), preoperative PTH (I 2 ¼ 92%, P < 0.0001) and preoperative calcium levels (I 2 ¼ 79%, P < 0.0009), a random-effects model was used for the meta-analyses. According to the heterogeneity for the meta-...…”
Section: Resultsmentioning
confidence: 99%
“…CI, confidence interval. 3,15,16,19,20,22,23,25,27,29,34 Figure 3. Forest plot of a meta-analysis to evaluate the relationship between preoperative vitamin D and the risk for postoperative hypocalcaemia after thyroidectomy in adult patients.…”
Section: Resultsmentioning
confidence: 99%